As veias abertas pelo dendê: efeitos na bacia hidrográfica do igarapé Ipitinga do assentamento Nazaré, Acará – Pará - COSTA, Dalva Maria Foro da (2021)
The development model that has been established in the field today has generated transformations that do not always take into account the specificities of this social space. This article aims to discuss, through a case study, the socio-environmental transformations that occurred from the implementation of mega entrepreneurship of the cultivation of the Guinean Elaeis palm in the territory that comprises the Nazaré Settlement, municipality of Acará, PA. The work was qualitative in nature, with documentary and bibliographic research, with field work, to monitor the situation of the Ipitinga stream and its tributaries and conducting interviews with 13 farmers of the Settlement. As a result, it is pointed out that oil palm, produced on a large scale, produced direct effects on water courses and transformed the daily lives of these peasants and changed the way they relate to the natural resources of their surroundings.